Consensus recommendations on managing the selected comorbidities including cardiovascular disease, osteoporosis, and interstitial lung disease in rheumatoid arthritis. Issue 1 (7th January 2022) - Yu, Kuang-Hui; Chen, Hsin-Hua; Cheng, Tien-Tsai; Jan, Yeong-Jian; Weng, Meng-Yu; Lin, Yeong-Jang; Chen, Hung-An; Cheng, Jui-Tseng; Huang, Kuang-Yung; Li, Ko-Jen; Su, Yu-Jih; Leong, Pui-Ying; et al.
Abstract: Background: Rheumatoid arthritis (RA)-related comorbidities, including cardiovascular disease (CVD), osteoporosis (OP), and interstitial lung disease (ILD), are sub-optimally managed. RA-related comorbidities affect disease control and lead to impairment in quality of life. We aimed to develop consensus recommendations for managing RA-related comorbidities. Methods: The consensus statements were formulated based on emerging evidence during a face-to-face meeting of Taiwan rheumatology experts and modified through three-round Delphi exercises. The quality of evidence and strength of recommendation of each statement were graded after a literature review, followed by voting for agreement. Through a review of English-language literature, we focused on the existing evidence of management of RA-related comorbidities. Results: Based on experts' consensus, eleven recommendations were developed. CVD risk should be assessed in patients at RA diagnosis, once every 5 years, and at changes in DMARDs therapy. Considering the detrimental effects of nonsteroidal anti-inflammatory drugs (NSAIDs) and corticosteroids on CVD risks, we recommend using the lowest possible dose of corticosteroids and prescribing NSAIDs cautiously. The OP/fragility fracture risk assessment includes dual-energy X-ray absorptiometry and fracture risk assessment (FRAX) in RA. The FRAX-based approach with intervention threshold is a useful strategy for managing OP. RA-ILD assessment includes risk factors, pulmonary function tests, HRCT imaging and a multidisciplinary decision approach to determine RA-ILD severity. A treat-to-target strategy would limit RA-related comorbidities. Conclusions: These consensus statements emphasize that adequate control of disease activity and the risk factors are needed for managing RA-related comorbidities, and may provide useful recommendations for rheumatologists on managing RA-related comorbidities.